Responses in cognitive hierarchy games are correlated with academic performance and the cognitive reflection test - Mantilla, César; Ortiz-Merchán, Silvia (Frontiers in Psychology, 2023)
Economics and Finance undergraduate students from four cohorts played LUPI, a game rewarding the person submitting the lowest unique positive integer, for a small bonus in an exam. Some months later, they played this game again with financial incentives and took a cognitive reflection test (CRT). We find that submitted responses to different configurations of LUPI are correlated with short-term (i.e., exam grade) and medium-term (i.e., final grade and GPA) academic performance, as well as the score in the CRT.